Leucocyte count and C-reactive protein cannot be relied upon in the diagnosis of acute appendicitis in HIV-infected patients. Issue 1 (9th January 2021) - Truter, M; Karusseit, V O L; Montwedi, D; Becker, P; Mokoena, T
Abstract: Background: South Africa has the highest prevalence of human immunodeficiency virus (HIV) infection in the world, and is commonly found in association with appendicitis. Atypical presentation of appendicitis in the presence of HIV infection makes clinical diagnosis of appendicitis unreliable, and inflammatory markers are commonly used as adjuncts. The aim of this study was ascertain the value of inflammatory markers in the diagnosis of appendicitis in patients with and without HIV infection. Methods: Patients with acute appendicitis were studied and divided into HIV-infected and HIV-uninfected groups. Symptoms, and systemic and local signs were recorded. Appendiceal pathology was classified as simple or as complicated by abscess, phlegmon or perforation. Total white cell count (WCC) and C-reactive protein (CRP) were chosen as inflammatory markers. Findings were compared between the two groups. Results: The study population consisted of 125 patients, of whom 26 (20.8 per cent) had HIV infection. Clinical manifestations did not differ statistically, and there was no difference in the incidence of simple or complicated appendicitis between the two groups. The mean CRP level was significantly higher in HIV-infected patients (194.9 mg/l versus 138.9 mg/l in HIV-uninfected patients; P  = 0.049), and mean WCC (x10 9 /L) was significantly lower (11.07 versus 14.17×10 9 /l respectively; P  = 0.010) Conclusion: Clinical manifestations and pathology did not differ between HIV-infected and HIV-uninfected patients with appendicitis, except that the WCC response was significantly attenuated and CRP levels were generally higher in the presence of HIV infection.